Sectoral wage and price formation and working time in Germany: An econometric analysis - Wolfgang Franz; Werner Smolny (Universität Konstanz, Forschungsschwerpunkt Internationale Arbeitsmarktforschung, 1993)
In this paper a variety of theories concerning the wage and price formation in Germany are tested. More specifically, wage and price equations are specified in a fairly general manner which nests several theoretical arguments (such as the target real wage bargaining model, hysteresis effects, outsider ineffectiveness, interindustry wage competition) and a perceived tradeoff between reductions in working time and wage increases. Related arguments hold for the price setting process. Recently developed econometric techniques such as error correction models are applied.
Keywords: J31; 330